Subtitling the Mafia and the Anti-Mafia from Italian into English: An Analysis of Cultural Transfer - Uzzo, Gabriele (Íkala, Revista de Lenguaje y Cultura, 2023)
Besides big Hollywood productions, like The Godfather trilogy, and video-on-demand productions, like The Sopranos, both filmed in English, new popular Italian productions, based on the linguistic and cultural representation of the Mafia and the Anti-Mafia, have gained momentum. Nonetheless, the body of academic research on the linguistic traits of the former is larger than research on the latter. This study aims to investigate how and by which strategies the lexicon and the culture-bound terms related to the concept of the Mafia and the Anti-Mafia are culturally transferred and subtitled from Italian into English. The TV series Vendetta: guerra nell’antimafia is used as the corpus for both a quantitative and a qualitative analysis. Results show that the translation of the Mafia and the Anti-Mafia for the purpose of audiovisual translation, through subtitling, is a simpler and less convoluted form of translation than written legal translation, aimed at conveying complex concepts in a simpler way.